Disaster recovery - Phillips, Brenda D.; Mincin, Jenny (New York, NY : Routledge, 2023)
"Now in its third edition, Disaster Recovery continues to serve as the most comprehensive book of its kind and will span the core areas that recovery managers and voluntary organizations must tackle after a disaster. It remains the go-to textbook for how to address and work through housing, donations, volunteer management, environmental recovery, historic and cultural resources, psychological needs, infrastructure and lifelines, economic recovery, public sector recovery, and much more. Special features include instructor's manual, PowerPoints, a free consultation with the authors upon adoption of the text; updated discussion questions; references and recommended readings; and updated resources for each chapter. New to the 3rd Edition A new co-author, Jenny Mincin, a recognized expert in international disaster recovery with direct field experience in emergency management, disaster recovery, and humanitarian relief to this text. New case examples from recent disasters and humanitarian crises will provide updated content and offer familiar events to readers (e.g., Hurricane María, the COVID-19 pandemic, active attackers). Increased visibility to the highest risk populations facing disaster recovery including refugees, immigrants, and asylees. New chapter on case management, which will be of particular interest to faculty in human services degree programs. Climate change as a hazard that requires adjustment before a disaster and during recovery. A broadened consideration of recovery needs including refugees and asylees fleeing both conflict and consensus disasters. This is an invaluable textbook in the field of recovery preparedness and execution"--
Includes bibliographical references and index.
Keywords: Emergency management -- United States; Disasters -- United States; Risk management -- United States; Hazard mitigation -- United States; Terrorism -- United States -- Prevention; Emergency management -- United States